Biological and behavioral correlates of body weight status among rural Northeast Brazilian schoolchildren. Issue 3 (17th January 2018) - dos Santos, Fernanda Karina; Moura dos Santos, Marcos André; Almeida, Marcelus Brito; Nobre, Isabele Goes; Nobre, Gabriela Goes; Ferreira e Silva, Wylla Tatiana; Gomes, Thayse Natacha; António Ribeiro Maia, José; Leandro, Carol Góis
Abstract: Objectives: The increase in the prevalence of overweight/obesity in youth is a public health problem worldwide; however, few studies have investigated its prevalence and correlates in children from the Brazilian Northeast region rural zone. The purpose of this study was (1) to estimate the prevalence of children's weight status according to sex, age, and birth weight categories; and (2) to investigate the links between biological and behavioral factors and weight categories. Methods: The sample comprises 501 children (248 girls), aged 7‐10 years, classified as low weight, normal weight, overweight, and obese using body mass index cut‐points. Predicted variables included birth weight, percentage of body fat (%BF), fat free mass (FFM), physical fitness, and gross motor coordination. Results: Data showed differences among weight groups for the predictor variables. Results of the logistic regression revealed that sex, age, %BF, FFM, physical fitness, and motor coordination seem to be relevant predictors of children's weight status, while no significant effect was observed for birth weight. Conclusion: Children with lower physical fitness levels as well as those with lower motor coordination quotient are more likely to be overweight and/or obese. No significant relationship was observed between birth weight and weight status in childhood. Strategies to reduce childhood obesity should consider biological, behavioral, and also environmental predictors.